Ethnomathematics-Based Pancasila Student Profile Strengthening Project Module in the Merdeka Curriculum Phase A in Elementary Schools - Midya Yuli Amreta; Giati Anisah (IKIP Mataram, 2023)
The transformation of education in Indonesia after Covid-19 has experienced quite significant changes, namely the latest Merdeka Belajar curriculum. The Merdeka Curriculum develops learning according to interests, learning styles and abilities that are connected to the competence of teachers and students. There are six competencies in Pancasila students formulated as key dimensions that are interrelated and strengthen each other, namely 1) faith, devotion to God Almighty and noble character, 2) global diversity, 3) mutual cooperation, 4) independence, 5) critical reasoning , and 6) creativity which then requires module development. This research aims to produce a product, namely a project module for strengthening the profile of Pancasila students which includes ethnomathematics. Etonmathematics means a module developed by integrating curriculum, pedagogy, mathematics and local wisdom. The use of local wisdom as an integrated module for the project to strengthen the profile of Pancasila students makes students trained and able to explore mathematical concepts that exist in their cultural environment. In this research, the context is local ethnomathematics wisdom in Tuban Regency, East Java. This research is Research and Development (R&D) research with a 4D model. 4D model design consists of four flows, namely Define, Design, Develop, and Desseminase. This development research was validated with 3 validators, namely design validator, language validator and material validator. The validation results from the design validation were 88%, which means it is suitable for use, the language validator is 94%, which means it is suitable for use, and the material validator is 90%, which means it is suitable for use. Then the module was tested on 48 phase A students. The average pretest result from trial 1 was 62.75, then in trial 2 it was 63.75. Followed by the posttest results from trial 1, namely 90.33 and trial 2, namely 91.58. After carrying out the pre-test and post-test at the trial stage, the researcher calculated the N-Gain Score value, namely N-Gain trial 1, namely getting a score of 0.76 which means high and getting an interpretation of N-Gain effectiveness of 76.78% which means effective. Then students filled out a student response questionnaire, and obtained presentation results of 85% in the very satisfied category. So it can be concluded that the project module for strengthening the profile of Pancasila students based on ethnomathematics in the Phase A independent curriculum in elementary schools that was developed is suitable for use and effective in learning mathematics.